Islands of Safety: Restoring Dignity in Violence-Prevention Work with Indigenous Families - Richardson, Cathy; Wade, Allan (First Peoples Child & Family Review, 2010)
Islands of Safety is a model and process designed in conjunction with Métis Community Services in Victoria, B.C. Based on a focus of human dignity and resistance, safety knowledges of women and Indigenous peoples, Islands of Safety was created by Métis family therapist Cathy Richardson and developer of response-based therapy Allan Wade. The initial stages of project design, pilot project implementation were funded by the Law Foundation of B.C. Resembling family group conferencing on the surface but rooted in different philosophical terrain, the Islands of Safety process is based on the understanding that people resist violence and prefer respect.